2011
DOI: 10.1266/ggs.86.231
|View full text |Cite
|
Sign up to set email alerts
|

Dissection and cytological mapping of barley chromosome 2H in the genetic background of common wheat

Abstract: We used gametocidal (Gc) chromosomes 2C and 3CSAT to dissect barley 2H added to common wheat. The Gc chromosome induces chromosomal breakage resulting in chromosomal aberrations in the progeny of the 2H addition line of common wheat carrying the monosomic Gc chromosome. We conducted in situ hybridization to select plants carrying structurally rearranged aberrant 2H chromosomes and characterized them by sequential C-banding and in situ hybridization. We established 66 dissection lines of common wheat carrying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Our study on cytological mapping of barley chromosome 3H revealed a discrepancy between the genetic and physical positions of the analyzed single-copy sequences, in line with previous data [Sorokin et al, 1994;Künzel et al, 2000;Serizawa et al, 2001;Künzel and Waugh, 2002;Joshi et al, 2011]. In distal regions, long genetic distances translated into short physical distances, indicating hot spots of recombination.…”
Section: Long Genetic Distances Translate Into Short Physical Distancsupporting
confidence: 87%
“…Our study on cytological mapping of barley chromosome 3H revealed a discrepancy between the genetic and physical positions of the analyzed single-copy sequences, in line with previous data [Sorokin et al, 1994;Künzel et al, 2000;Serizawa et al, 2001;Künzel and Waugh, 2002;Joshi et al, 2011]. In distal regions, long genetic distances translated into short physical distances, indicating hot spots of recombination.…”
Section: Long Genetic Distances Translate Into Short Physical Distancsupporting
confidence: 87%
“…8.4 ). The Gc system was successfully applied to produce dissection lines of various alien chromosomes in common wheat, such as barley chromosomes (2H, Joshi et al 2011 ;3H, Sakai et al 2009 ;4H, Sakata et al 2010 ;5H, Ashida et al 2007 ;7H, Masoudi-Nejad et al 2005 ), rye 1R chromosomes (Tsuchida et al 2008 ;Gyawali et al 2009Gyawali et al , 2010 and rye B chromosomes (Endo et al 2008 ). All possible kinds of rearrangements of alien chromosomes have been obtained (Fig.…”
Section: Dissection Of Alien Chromosomesmentioning
confidence: 99%
“…Using the Gc system, Endo and his colleagues have dissected the barley chromosomes in the addition lines of common wheat (Shi and Endo, 1997, 1999, and constructed cytological maps for five barley chromosomes using various DNA markers: 2H with ESTs (Joshi et al, 2011), 3H with ESTs (Sakai et al, 2009), 4H with ESTs (Sakata et al, 2010), 5H with ESTs (Ashida et al, 2007), 7H with AFLPs and STSs (Serizawa et al, 2001), 7H with AFLPs and SSR (Masoudi-Nejad et al, 2005), and 7H with ESTs .…”
Section: Introductionmentioning
confidence: 99%